Kearifan Lokal Mitos Pertanian Dewi Sri dalam Naskah Jawa dan Aktualisasinya sebagai Perekat Kesatuan Bangsa - Trisna Kumala Satya Dewi; Heru Supriyadi; Sholeh Dasuki (Manuskripta, 2018)
The agricultural myth of "Dewi Sri" contained in Javanese manuscripts contains local wisdom related to agriculture, fertility, food (rice) and actualized in the ritual of village cleaning (bersih desa) ceremonies. The term of village cleaning is also commonly referred to as sadran (nyadran), ruwah rosul, sedekah bumi, and manganan. In the ritual of village cleaning ceremonies some Javanese people still actuaize it with performng art of the Wayang Purwa with the lakon of Sri Sadana or Sri Mulih (Mbok Sri Boyong). In addition, there are also some people who implement village cleaning with Tayub performing arts. The performing arts in the ritual of village cleaning are the actualization of the agricultural myth, namely "Dewi Sri" as a symbol of "Goddess of Rice", "Goddess of Fertility". The ritual of village cleaning as local wisdom can be used as a social adhesive in the community (Java). Besides that, in the village cleaning there are also various functions such as expressing gratitude to the Almighty God for salvation and abundance of sustenance, fostering togetherness (harmony), and tolerance between citizens. --- Mitos pertanian Dewi Sri yang termuat dalam naskah-naskah Jawa mengandung kearifan lokal yang berkaitan dengan pertanian, kesuburan, pangan (padi) dan diaktualisasikan dalam upacara ritual bersih desa. Istilah bersih desa biasa juga disebut dengan sadran (nyadran), ruwah rosul, sedekah bumi, dan manganan. Dalam upacara ritual bersih desa sebagian masyarakat Jawa masih mempagelarkan dengan seni wayang purwa dengan lakon Sri Sadana atau Sri Mulih (Mbok Sri Boyong). Di samping itu, juga ada sebagian masyarakat yang melaksanakan bersih desa dengan seni pertunjukan tayub. Seni pertunjukan dalam ritual bersih desa tersebut merupakan aktualisasi mitos pertanian, yaitu “Dewi Sri” sebagai simbol “Dewi Padi”, “Dewi Kesuburan”. Upacara ritual bersih desa sebagai kearifan lokal tersebut dapat digunakan sebagai perekat sosial dalam masyarakat (Jawa). Selain itu, dalam bersih desa juga termuat berbagai fungsi seperti ungkapan rasa syukur kepada Tuhan Yang Mahakuasa atas keselamatan dan limpahan rezeki, memupuk kebersamaan (guyub rukun), dan toleransi antarwarga.